2019
DOI: 10.1165/rcmb.2018-0152oc
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Fatty Acid Oxidation in Alveolar Epithelial Cells Mediates Acute Lung Injury

Abstract: Profound impairment in cellular oxygen consumption, named cytopathic dysoxia, is one of the pathological hallmarks in the lungs of patients with pathogen-induced acute lung injury (ALI). However, the underlying mechanism for this functional defect remains largely unexplored. In this study, we found that primary mouse alveolar epithelial cells (AECs) conducted robust fatty acid oxidation (FAO). More importantly, FAO was strikingly impaired in AECs of mice with lipopolysaccharide (LPS) induced ALI. The metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 46 publications
1
69
0
Order By: Relevance
“…Similar to the findings of previous studies of M. tuberculosis and M. bovis BCG [20], we found that PPARα deficiency increased the levels of proinflammatory cytokines and chemokines in the lung and macrophages during Mabc infection. These findings are in partial agreement with a recent report of a protective role of PPARα activation against lipopolysaccharide-induced acute lung injury in mice [11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar to the findings of previous studies of M. tuberculosis and M. bovis BCG [20], we found that PPARα deficiency increased the levels of proinflammatory cytokines and chemokines in the lung and macrophages during Mabc infection. These findings are in partial agreement with a recent report of a protective role of PPARα activation against lipopolysaccharide-induced acute lung injury in mice [11].…”
Section: Discussionsupporting
confidence: 93%
“…Due to its regulation of macrophage-mediated inflammation, PPARα is a promising target for various human pathologies, particularly cardiovascular and metabolic diseases [9,10]. In addition, PPARα expression is involved in protective role against numerous disease models including acute lung injury [11], sepsis-associated acute kidney injury [12], non-alcoholic steatohepatitis [13], etc. Indeed, PPARα as well as PPARγ play crucial roles in the modulation of host defenses against a variety of microbial infections [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model of acute pulmonary endotoxemia-induced damage, alveolar epithelial cells show decreased expression of genes involved in mitochondrial biogenesis and fatty acid oxidation, including Ppargc1a and Cpt1a, as well as impaired fatty acid oxidation. The deletion of Ppargc1a, the gene encoding PGC-1A, from alveolar epithelial cells renders mice more susceptible to pulmonary damage caused by intranasal treatment with LPS, an effect associated with increased caspase-3 cleavage in epithelial cells, thus suggesting that the absence of fatty acid oxidation in the alveolar epithelial cells is necessary for the survival of these cells in response to acute lung injury 81 . PGC-1A cooperates with PPARα in the transcriptional control of nuclear genes encoding mitochondrial fatty acid oxidation enzymes, thereby inducing fatty acid oxidation 82 .…”
Section: Antivirulence Metabolic Strategies To Block Pathogenic Signalsmentioning
confidence: 99%
“…PGC-1A cooperates with PPARα in the transcriptional control of nuclear genes encoding mitochondrial fatty acid oxidation enzymes, thereby inducing fatty acid oxidation 82 . The treatment of mice with a PPARα agonist is sufficient to protect against LPS-induced lung injury; consequently, PGC-1A may promote disease tolerance in response to acute lung injury by promoting fatty acid oxidation in alveolar epithelial cells and consequently protect against cell death 81 . Therefore, promoting fatty acid oxidation in alveolar epithelial cells may be useful for increasing survival in patients with COVID-19 by maintaining the epithelial barrier.…”
Section: Antivirulence Metabolic Strategies To Block Pathogenic Signalsmentioning
confidence: 99%
“…Bundles of studies observed mitochondrial dysfunction of airway epithelial cells (AECs) in ALI/ARDS. 5,9,10 Moreover, rescuing AECs from mitochondrial dysfunction through mitochondria transferring relieved LPS-induced ALI. 11 A more recent report also affirmed that compensation for mitochondrial impairment by enhancing cellular glycolytic activity could protect airway epithelium from acute injury.…”
Section: Introductionmentioning
confidence: 99%